Plants are Not Sitting Ducks: Teaching Module on Plant Biochemical Interactions with Insects. Issue 1 (15th June 2017) - Smith, Jason D.; Kariyat, Rupesh R.
Abstract : Core Ideas: Plant–caterpillar bioassays are ideal, low‐cost research tools to investigate plant–herbivore interactions and underlying genetic, chemical, and physical aspects of plant biology. We present methods and results for a caterpillar bioassay that was conducted by students in an introductory biology class. This teaching module illustrates: (1) genetic control of plant defense traits in Arabidopsis thaliana, (2) the importance of chemicals in biological/ecological interactions, and (3) the interplay of plant defenses and herbivore responses. The widespread misperception of plants as passive organisms—providing the backdrop against which the more active members of the animal kingdom play out the drama of life—presents both a challenge and an opportunity for integrating plant science into classrooms. The challenge is to show students that plants are, in fact, lively organisms that actively perceive and respond to their environments. And, the opportunity is that understanding plant community interactions can provide students a window onto the hidden complexity of the living world. Here, using ecological knowledge derived from chemical ecology and molecular genetics, we present a hands‐on teaching module that illustrates plants' defenses at work against insect herbivores with bioassays that can be accomplished without any specialized laboratory equipment. Using caterpillar preference as an indicator of plant defense status, students can observe the differential defense abilities of wild‐type and mutant Arabidopsis thaliana (Brassicaceae) lines that vary in their production of defense compounds (glucosinolates). To demonstrate the feasibility of these assays in a biology classroom, we present student‐generated data from experiments that were performed in an undergraduate biology class. We gauged the effectiveness of the teaching module with a Likert survey, which indicated that students enjoyed the investigation and achieved our learning goals with regard to plant biology and ecology. This module can be tailored to different education levels and can effectively elucidate a wide range of basic and advanced life‐science concepts, ranging from the ecology and biochemistry of trophic interactions to adaptation and co‐evolution.